2008
DOI: 10.1159/000165381
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Uncinate Fasciculus in Memory and Emotional Recognition in Amnestic Mild Cognitive Impairment

Abstract: Background: The putative neural bases of affected episodic memory and emotional recognition in early Alzheimer’s disease are suspected to be limbic and paralimbic pathological processes. The uncinate fasciculus (UF) is especially considered to be a critical structure. In the present study, we investigated microstructural UF pathology by diffusion tensor imaging in the subjects with amnestic mild cognitive impairment (aMCI), and its association with memory and emotional processing impairment. Methods: Subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 71 publications
8
94
0
Order By: Relevance
“…32 Previous diffusion tensor imaging studies, investigating one or the other tract in isolation, have shown correlations with episodic memory. 33,34 The present study extends these findings substantially both by demonstrating specificity of association-by comparison with both a control tract and control cognitive domains-and by assessing associations with multiple pathways of temporal interaction simultaneously. This is important because lesion studies in monkeys show that the significance of some connections for memory can be appreciated only when other pathways of interaction with the temporal lobe have been disconnected.…”
supporting
confidence: 62%
“…32 Previous diffusion tensor imaging studies, investigating one or the other tract in isolation, have shown correlations with episodic memory. 33,34 The present study extends these findings substantially both by demonstrating specificity of association-by comparison with both a control tract and control cognitive domains-and by assessing associations with multiple pathways of temporal interaction simultaneously. This is important because lesion studies in monkeys show that the significance of some connections for memory can be appreciated only when other pathways of interaction with the temporal lobe have been disconnected.…”
supporting
confidence: 62%
“…In fact, the UF, which occupies the white matter of the orbital and medial frontal structures and connects the temporal and prefrontal areas, is thought to play a crucial role in the regulation of emotional responses and in attaching emotional valence to visual information [35,36]. Furthermore, Fuji and colleagues [37] found that changes in the UF microstructure of a-MCI subjects were not only associated with memory impairment but also with emotional processing impairment, specifically emotional facial recognition. The ILF, which constitutes the association sys-tem of ventral visual pathways in the occipito-temporal cortices, is involved in emotional processing [35]; its disruption causes agnosia and prosopagnosia [36].…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, MD and FA show a significant association with cognitive functions typically impaired in AD and MCI, including mental status (e.g., [30,31,35,50,59,66,91,93]) suggesting external validity of these measures because of their relationship to cognitive performance and group differences.…”
Section: Discussionmentioning
confidence: 99%
“…Fujie et al [35] found that FA in the uncinate fasciculus, a pathway that connects the frontal and temporal lobes, was significantly reduced in MCI compared to healthy controls and that FA in this fasciculus in MCI was significantly correlated with memory performance. Stricker el al.…”
Section: Investigations Of Targeted Regions Involved In Memory Procesmentioning
confidence: 99%